Systematic Review of Electroacupuncture for Bell’s Palsy - Min-seok Go; Seong-hyun Lee; Ji-eun Oh; Seung-chul Yeom; Tae-ha Kwon; Sae-young Bong; Cha-young Lee; Hye-jin Shin (Journal of Acupuncture Research)
Bell’s palsy, characterized by sudden-onset facial paralysis of unknown cause, is the most prevalent form of its kind, and electroacupuncture (EA) is one of the popular treatments in Korea. This review aimed to evaluate the effectiveness of EA in treatingBell’s palsy. Among the randomized controlled trials (RCTs) targeting patients with Bell’s palsy, studies comparing EA treatment with other therapies in PubMed, OVID, Cochrane RCTs, and China National Knowledge Infrastructure were searched up to April 2024. Data extraction and risk-of-bias assessment were performed independently. For the primary outcome, the House-Brackmann facial nerve grading system was used, and a significant difference was found in the EA group, although the results were inconsistent across all three studies. Secondary outcomes, including the total effective rate and recovery duration, generally favored EA, with some studies reporting significant differences compared with the control groups. The quality of evidence, evaluated by the grading of recommendations assessment and the development and evaluation approach, was moderate to low. This systematic review proposes that EA may be partially effective on Bell’s palsy and shortening the recovery time. However, further high-quality RCTs are needed to confirm these findings and address the limitations identified in the current evidence.